35/4 square meters by 7/2 meters

Answers

Answer 1
Answer: Area = 35/4  m²

Length = 7/2 m

Area =  length * width

35/4 =  7/2 * width

7/2 * width = 35/4

width = 35/4 ÷ 7/2

width = 35/4  × 2/7 = 5/2

Width = 5/2 m

Related Questions

A bathroom is 6 ft 5in long and 4 ft 3in wide what is the area of the bathroom in square feet. I need work with the answer
Does a triangle equal to 180° or 360°?
This year, 40 students tried out for the softball team. Last year, 8 fewer students tried out. What is the percent increase in the number of students who tried out for the softball team?
Someone please solve & explain
You are creating identical candy bags using 18 chocolate bars and 30 peanut butter cups. What is the greatest number of bags you can fill using all the candy? Show your work

a)postos pelo vértice b )adjacentes suplementares c ) congruentes e não opostos pelo vértice d )suplementares e não adjacentes

Answers

i can not read this because it is a different language sorry

What is 95% of 35?
A.52.25
B.33.25
C.19
D.38

Answers

The answer is B (33.25)

Finding the answer is very easy. You first need to divide 95% by 100 to get .95. Then, multiply .95 by 35 to get 33.25.

An increase in temperature of 10 degrees on the Celsius scale corresponds to an increase of how many degrees on the Fahrenheit scale

Answers

10 degrees C is equal to 50 degrees F 

Answer: 50

Step-by-step explanation: The equation of Celsius to Fahrenheit is multiply by 1.8 (or 9/5) and add 32.

An athlete jumped 5.5 feet which was 1.1 times higher than the previous jumper how high did the previous athlete jump

Answers

Answer:

5 ft

Step-by-step explanation:

The previous jumper jumped p

The new jumper jumped p*1.1 and that was 5.5 ft

1.1p = 5

Divide each side by 1.1

1.1p/1.1 = 5.5/1.1

p = 5

The previous jumper jumped 5 ft

Answer:

5 ft

Step-by-step explanation:

Let the height of the previous jump be represented by j.  Then 1.1j = 5.5 ft.

Dividing both sides by 1.1, we get j = 5 ft.  This was the height of the previous jump.

25 PTS!!!!y = 3x + 3 y = x − 1 Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form

Answers

remember that you can do anything to an equaiton as long as you do it to both sides
ok so subsitution
basiclalyy you subsitute a known thing for an unknown thing so
y=3x+3 and y=x-1
they both equal y so
3x+3=y=x-1
3x+3=x-1
subtract x from both sides
2x+3=-1
subtract 3 from bot sides
2x=-4
divide both sides by 2
x=-2
subsitute
y=x-1
y=-2-1
y=-3

the solution is x=-2 y=-3 so
(x,y)
(-2,-3)

Malkia is thinking of a mystery number. She cuts it in half then adds 5. The result is 24. Determine the mystery number. I need the answer​

Answers

Answer:38

Step-by-step explanation:if you take 24 and subtract the five she added, it gives you 19 and since she divided it by two you would multiply it by two to get the original number she was thinking of

Hope this helps :)

Answer:

38

Step-by-step explanation:

38 divided by 2 would equal to 19, plus 5 would be 25.